A monoclonal antibody raised against Acinetobacter baumannii capsular carbohydrate exhibits cross-species in vitro binding against Pseudomonas aeruginosa - Matthew Slarve; Hadley Jaramillo; Brian Luna; Brad Spellberg (PLoS ONE, 2026)
The emergence of extensively drug-resistant bacterial pathogens such as Acinetobacter baumannii and Pseudomonas aeruginosa necessitates the innovation of non-small molecule therapies. Monoclonal antibodies represent a promising non-small molecule option. By exploiting shared or similar antigenic structures on these pathogens, it may be possible to develop therapeutic antibodies that target both bacterial species. Here we demonstrate that a previously developed monoclonal antibody targeting A. baumannii (MAb10) has cross-species reactivity to P. aeruginosa in in vitro assays. Despite MAb10’s distinct efficacy against A. baumannii , no efficacy was detected against P. aeruginosa in our mouse models of infection. Nevertheless, the unique carbohydrate structures targeted by MAb10 and shared by numerous bacterial species may underscore a possible strategy for developing therapeutic antibodies that can treat infections caused by multiple pathogens.